Odpowiedzi

  • Roma
  • Community Manager
2010-02-27T16:03:17+01:00
7x + 5 > 6x + 3
7x - 6x > 3 - 5
x > - 2
x ∈ (-2; +∞)

12x - 9 < 8x - 7
12x - 8x < - 7 + 9
4x < 2 /: 4
x < ½
x ∈ (- ∞; ½)

- 4x + 11 ≥ 19
- 4x ≥ 19 - 11
- 4x ≥ 8 /: (-4)
x ≤ - 2
x ∈ (- ∞; - 2>

- 4x < -3x - 2
- 4x + 3x < - 2
- x < - 2 /*(-1)
x > 2
x ∈ (2; +∞)
2010-02-27T17:27:25+01:00

7x + 5 > 6x + 3

12x - 9 < 8x - 7

-4x + 11 ≥ 19

-4x < -3x - 2


7x + 5 > 6x + 3
x>-2

12x - 9 < 8x - 7
4x<2 /:4
x< ½

-4x + 11 ≥ 19
-4x≥8 /:(-4)
x ≤-2

-4x < -3x - 2
-x<-2/:(-1)
x>2